Investigating rates and mechanisms of lateral erosion in a small bedrock river using erosion pins, structure-from-motion photogrammetry, and optically stimulated luminescence dating: Konza Prairie, northeast Kansas - Marcotte, Abbey Leigh (Kansas State University, 2020)
Bedrock rivers play a critical role in landscape evolution by leaving signatures of past climate shifts, base level changes, and tectonic uplift in the landscape. While much is known about the mechanics of vertical bedrock incision, the fluvial processes driving lateral bedrock erosion and the timescales over which it occurs remain poorly understood. In order to advance our understanding of how bedrock rivers erode laterally over time, I investigated past and present erosion rates at Kings Creek, an incised stream in northeast Kansas, U.S.A. This system consists of horizontally bedded alternating layers of limestone and shale, presenting a unique setting to study rates and mechanisms of lateral bedrock erosion. Erosion pins and structure from motion (SfM) were used to determine annual lateral erosion rates and spatio-temporal patterns of erosion along bedrock channel banks. Single-grain optically stimulated luminescence (OSL) dating of fluvial deposits overlying a strath terrace was used to determine the depositional age of fluvial deposits and infer the duration of lateral channel mobility during terrace occupation. Lateral erosion rates of limestone measured during this study averaged 20.82 mm/yr and shale lateral erosion rates range from 38.81 – 53.41 mm/yr. Field observations indicate that plucking is the dominant erosion mechanism in both lithologies. These modern lateral bedrock erosion rates are much higher than originally anticipated owing to several high magnitude flow events during an exceptionally wet year. The OSL ages of fluvial deposits sourced from the strath terrace suggest that Kings Creek experienced periods of aggradation, incision, and channel migration during the late Pleistocene. Together, the annual erosion rates and OSL ages provide information about rates of lateral erosion and paleochannel mobility, thus improving our understanding of the timing and processes linked to how bedrock rivers erode laterally to form wide bedrock valleys
Keywords: Bedrock rivers; Luminescence dating; Structure from motion photogrammetry; Erosion pins; Strath terraces; Lateral bedrock erosion